T-Type Multi-Inverter Application for Traction Motor Control - Ha, V. T.; Giang, P. T.; Phuong, V. H. (Engineering, Technology & Applied Science Research, 2022)
The structure and principle of the T-type 3-level reverse voltage source that will be fed to three-phase induction motors will be presented in this study. The implementation of Space Vector Pulse Width Modulation (SVPWM) and the math models of the induction motor, the stator currents, and the speed controller design of the electric traction drive system based on Field-Oriented Control (FOC) will be also shown. This three-level T-type inverter in the FOC structure decreases Total Harmonic Distortion (THD) more than the previous two-level inverters. By combining the FOC control structure with the T-type 3-level inverter, the speed and torque responses necessary for railway traction motor load were improved. Finally, Matlab/Simulink will be used to demonstrate the correctness of the T-Type multi-level inverter theory.